HOW POST-POSITIVISM INFLUENCES SCIENCES EDUCATION IN ELEMENTARY SCHOOLS - Sriwarthini, Nina (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research examines the influence of post-positivism on science education in Indonesia, focusing on its implications for elementary schools. The study adopts a qualitative approach, utilizing literature review (library research) as its methodology to gather data from various relevant sources (Kartiningrum, 2015). Post-positivism, which emerged as a modification of positivism, challenges the notion of absolute scientific truth and emphasizes the importance of subjectivity in understanding reality. In the context of education, this philosophical shift promotes a more critical, reflective approach to teaching science, encouraging students to question, analyze, and think critically rather than accept scientific knowledge as fixed. However, the integration of post-positivism in Indonesian science education raises concerns, particularly regarding the potential sidelining of spiritual, moral, and ethical values that are deeply embedded in the educational system. As the curriculum becomes more focused on empirical evidence and scientific reasoning, there is a risk that these values could be overshadowed. Despite this, post-positivism offers several benefits, including fostering problem-solving skills and adaptability in students. By analyzing the role of post-positivism within the Indonesian education system, this study provides insight into the advantages and challenges of integrating this philosophical approach into science education, while also considering the balance needed between scientific inquiry and the preservation of cultural and spiritual values. The findings suggest that a careful, context-sensitive application of post-positivism is essential for fostering a holistic educational experience.